2020
DOI: 10.1080/20009666.2020.1798141
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of CRP and D-Dimer levels for in-hospital outcomes and mortality of COVID-19

Abstract: Background: Systemic inflammation elicited by a cytokine storm is considered a hallmark of coronavirus disease 2019 (COVID-19). This study aims to assess the clinical utility of the C-reactive protein (CRP) and D-Dimer levels for predicting in-hospital outcomes in COVID-19. Methods: A retrospective cohort study was performed to determine the association of CRP and D-Dimer with the need for invasive mechanical ventilation (IMV), dialysis, upgrade to an intensive care unit (ICU) and mortality. Independent t-test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
39
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 14 publications
11
39
5
Order By: Relevance
“…Inflammatory markers, such as CRP and d-dimer, performed after hospital admission, were found to be positively associated with both disease severity and multiple antibiotic prescribing among survey patients. This finding corroborates previous research findings where it was found that increased CRP and d-dimer is positively associated with poor patient outcomes [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory markers, such as CRP and d-dimer, performed after hospital admission, were found to be positively associated with both disease severity and multiple antibiotic prescribing among survey patients. This finding corroborates previous research findings where it was found that increased CRP and d-dimer is positively associated with poor patient outcomes [ 14 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, mean CRP levels were significantly higher in the groups of patients needing critical care than those with the less progressed disorder at admission and on day 7. Although, in contrast to our results, the researchers failed to find a significant relationship between on-admission CRP levels and the odds of mortality, increased levels of this factor (> 101 mg/dl) on day 7 was associated with elevated COVID-19 mortality risk (OR = 3.7; 95% CI = 1.1-12.5) than the patients with < 100 mg/dl CRP levels after adjusting for comorbidities at baseline and medications consumption [32].…”
Section: The Inflammatory Marker and Covid-19 Mortalitycontrasting
confidence: 99%
“…A systematic review and meta-analysis on 16 studies, including 1896 survivors and 849 non-survivors COVID-19 cases, documented that serum levels of CRP of non-survivor patients was significantly greater than the survivors (standard difference in means = 1.371) [30]. A retrospective cohort study of 176 patients with COVID-19 showed partially similar results to the present findings [32]. Although no significant differences in serum CRP levels of COVID-19 survivors and non-survivors were found on admission, on day 7, a greater mean CRP was related to elevated mortality.…”
Section: The Inflammatory Marker and Covid-19 Mortalitysupporting
confidence: 86%
See 2 more Smart Citations